2001
DOI: 10.1080/016502501316934897
|View full text |Cite
|
Sign up to set email alerts
|

Audio recording of infant crying: Comparison with maternal cry logs

Abstract: This study investigated the accuracy of mothers' reports of their babies' crying. The crying of babies, 5-16 weeks old, was recorded by means of a wire-less, miniature microphone contained within a terry cloth belt worn by the baby. Crying was transmitted to a voice-activated recorder with a range of 500 feet. Thirteen 24-hour recordings were obtained from seven infants while, at the same time, the mothers kept a Cry Log of their baby's crying. The number of minutes of crying and the number of bouts of crying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies have found that reports on a cry diary are related to audiotaped recordings, providing evidence for the validity of the cry diary (St. James-Roberts et al, 1993; Salisbury, Minard, Hunsley, & Thoman, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that reports on a cry diary are related to audiotaped recordings, providing evidence for the validity of the cry diary (St. James-Roberts et al, 1993; Salisbury, Minard, Hunsley, & Thoman, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four hour behavior diaries are considered to be the international gold standard for measurement. 14,[34][35][36] We investigated, firstly, what is the change in fuss/cry duration over the first 12 weeks of life and is there a universal "crying curve" (5-6 week fuss/cry duration peak)?…”
Section: Introductionmentioning
confidence: 99%
“…There might be some variability in the accuracy of both parents’ and nurses’ recording. There is a considerable literature on the reliability of parental verbal or questionnaire report of their infant’s behaviour and temperament (13,14), and parent’s documentation of 24 h cycles of their infant’s cry and sleep patterns (15). Reliability estimates vary, but depending on what infant information or behaviour parents’ document, the estimates are in the 50–85% range compared with an independent measure of the infant or child’s behaviour in question.…”
mentioning
confidence: 99%